Isolation and Identification of Bacteriocin-producing Bacillus subtilis S1-2 from Soybean Paste and Its Stability Study - Taowei ZHANG; Rina WU; Shuaiqi JI; Mengxue LOU; Ying MA; Junrui WU (Shipin gongye ke-ji, 2024)
In this study, a strain with good antibacterial effect was screened and identified from traditional soybean paste in Northeast China. The strain was identified using methods such as 16S rDNA and housekeeping gene gyrA sequencing analysis. Its bacteriocins were crude extracted using ethyl acetate extraction, further purified using dextran gel Sephadex-G50 and high performance liquid chromatography (HPLC) techniques, combined with SDS-PAGE and liquid chromatography-mass spectrometry (LC-MS/MS) for identification. The antibacterial effect of the bacteriocin on Staphylococcus aureus was analyzed by determining the minimum concentration and growth inhibition curve. Additionally, the stability of the bacteriocins was investigated by exploring its thermal stability, pH tolerance, and resistance to proteases. Results showed that the Bacillus subtilis S1-2 strain had the best antibacterial effect on Staphylococcus aureus and Listeria monocytogenes. The bacteriocin produced by the strain was identified as subtilosin A, with molecular weight of approximately 3 kDa, and demonstrated a significant inhibitory effect on Staphylococcus aureus and Listeria monocytogenes. The minimum inhibitory concentration against Staphylococcus aureus was 0.625 mg/mL. Furthermore, the bacteriocin exhibited stable antibacterial activity between 20~80 ℃ and even between 100~120 ℃. It showed the highest antibacterial activity in the pH range of 6.0~8.0, as well as good acid and alkali tolerance with pH values of 1 and 10. Furthermore, it could be hydrolyzed by proteinase K, pepsin, and trypsin. In conclusion, Bacillus subtilis S1-2 and its bacteriocin subtilosin A have great potential in food preservation due to their strong antibacterial activities.